The vigilant investor : a former SEC enforcer reveals how to fraud-proof your investments - Huddleston, Pat. (New York : American Management Association, 2012)
Huddleston explains why we fall for investment scams, how con artists play on the human tendencies we all share, and what we can do to protect ourselves from predators.
Includes bibliographical references and index.
Keywords: Investments; Securities fraud; Swindlers and swindling -- Prevention